Sustainable Agricultural Development: Challenges and Approaches in Southern and Eastern Mediterranean Countries - Petit, M (Springer, 2015)
This book provides an up-to-date assessment of sustainable agri-food systems and rural development in the Mediterranean countries. It examines and reviews the impact of EU and national policies on environmental and trade issues in agricultural and rural organizations in the southern and eastern Mediterranean region. The book also reflects key socio-economic and political issues such as resource management, income distribution, employment and migration trends, and sustainability aspects. It demonstrates technical and methodological tools used for the analysis and explains their application. The book presents the collective work of a research consortium funded by an EU (FP7) project